Drug Utilization Evaluation of Lorazepam in Alcohol Withdrawal Syndrome Patients: A Secondary Care Teaching Hospital Based Study - Varghese, Divine; Ashok, Purnima; Nayak, Shristi; Jacob, Atul Aby; Dev, K. Vishnu; Thollur, Vijeesh (Journal of Drug Delivery and Therapeutics, 2020)
Background: Drug utilization evaluation is an important parameter for the safe, effective and rational use of medications in medical care. Alcoholism results in abundant cases of alcohol withdrawal which can prove to be life-threatening if untreated, lorazepam is a drug of choice for Alcohol Withdrawal Syndrome and requires close monitoring as its over-dosing or under-dosing is common in case of withdrawal. Objective: ensures the safe and rational use of Lorazepam in the management of Alcohol Withdrawal Syndrome. Materials and Method: This prospective, observational study was conducted among alcoholic patients admitted in the KC General Hospital, Karnataka, India. Baseline data for Clinical Institute Withdrawal Assessment for Alcohol revised scale (CIWA-Ar) was collected on the day of admission and the response to lorazepam treatment was recorded using the same with respect to the baseline data every 12th hourly after the initial administration until withdrawn. Results: Statistical analysis for 72 patients was done using ANOVA to calculate the overall progression of the syndrome with treatment. Among 72 patients 94.44% were male and 5.55% were female. The mean age of patients reported with AWS was found to be 44.90 years. A significant CIWA-Ar score reduction was observed with a p-value of <0.0001. Conclusion: Our study revealed a strong predominance of male patients with alcohol withdrawal syndrome, where maximum patients started consuming alcohol before the age of 20 years. After the administration of lorazepam, a significant CIWA-Ar score reduction was observed. Keywords: Alcohol Withdrawal Syndrome, CIWA-Ar scale, Drug utilization evaluation, Lorazepam.